2020
DOI: 10.1111/cgf.14048
|View full text |Cite
|
Sign up to set email alerts
|

DockVis: Visual Analysis of Molecular Docking Trajectories

Abstract: Computation of trajectories for ligand binding and unbinding via protein tunnels and channels is important for predicting possible protein–ligand interactions. These highly complex processes can be simulated by several software tools, which provide biochemists with valuable information for drug design or protein engineering applications. This paper focuses on aiding this exploration process by introducing the DockVis visual analysis tool. DockVis operates with the multivariate output data from one of the lates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 58 publications
(69 reference statements)
0
3
0
1
Order By: Relevance
“…The tool includes a graphical analysis feature with statistical reports on the frequency and distribution of each type of atom and interaction. Additionally, ( Furmanová et al, 2020 ), introduce DockVis as a visual analysis tool designed to work with multivariate output data from CaverDock ( Filipovič et al, 2019 ). DockVis provides interconnected 2D and 3D views, allowing to comprehend the spatial configurations of ligands as they traverse protein tunnels.…”
Section: General Considerations On Visualization Of Complex Molecular...mentioning
confidence: 99%
“…The tool includes a graphical analysis feature with statistical reports on the frequency and distribution of each type of atom and interaction. Additionally, ( Furmanová et al, 2020 ), introduce DockVis as a visual analysis tool designed to work with multivariate output data from CaverDock ( Filipovič et al, 2019 ). DockVis provides interconnected 2D and 3D views, allowing to comprehend the spatial configurations of ligands as they traverse protein tunnels.…”
Section: General Considerations On Visualization Of Complex Molecular...mentioning
confidence: 99%
“…Byška 等 [48] 提出了基于 Focus+Context 的交 互式视觉分析方法, 用于长时间和密集的分子动 力学模拟分析. Furmanová 等 [49] 提出了分子对接轨 迹的可视化分析工具 DockVis, 使用分子对接工具 CaverDock [50] 的输出数据, 将配体及周围环境用 二三维结合的形式描述. 用户利用该工具能快速 感知蛋白质隧道中配体的空间构象, 并与视图交 互开展信息钻取.…”
Section: 动态分子结构可视分析技术unclassified
“…Passage of substrates, intermediates, and products via molecular channels reduces the transit time to or from the active centers and facilitates an efficient transference within multifunctional enzymes or enzymatic complexes. Ligand transport, molecular docking trajectories, and the potential of molecular tunnels and channels in biotechnology have been recently analyzed [ 10 , 11 ]. Holding substrates in protein empty spaces can ensure substrate availability and loss of reaction intermediates by diffusion, thus increasing reaction efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…A simple strategy to allow the growth of thermophiles maintaining the thermal stability of labile biomolecules was recently proposed by Cuecas et al [ 12 ]. These authors concluded that maintaining intracellular viscosity can provide thermal stability to some low-molecular-weight biomolecules although this mechanism appeared to be inefficient above 80 °C [ 10 ]. Thus, hyperthermophiles might require additional adaptations and some complementary alternatives have been proposed [ 12 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%